Characterization of Polymer Structure at Buried Interfaces in Films by X-ray Photoelectron Spectroscopy Combined with Gas Cluster Ion Beam - Saeki, Shintaro (Langmuir : the ACS journal of surfaces and colloids, 2025)
Understanding the aggregation states of polymers at various interfaces, especially buried interfaces, is of pivotal importance not only from an inherent academic interest but also for the design and construction of functional materials and devices. However, precise analysis through laboratory-scale experiments remains challenging. In this study, we focused on X-ray photoelectron spectroscopy combined with a gas cluster ion beam (GCIB/XPS). First, the interfacial width of a polymer bilayer along the normal direction was evaluated using this method and compared with values obtained from neutron reflectivity experiments and theoretical calculations. This makes it clear that GCIB/XPS is well-suited for depth profiling of polymer interfaces at the nanometer scale under appropriate conditions. Building on this information, we applied the method to an epoxy resin adhered to a copper substrate, revealing that amine hardener molecules were segregated at the adhered interface. This study highlights that GCIB/XPS, despite being destructive, is a powerful tool for the structural analysis of buried polymer interfaces, and further advancements in this field are highly anticipated